STABILITY TESTING OF AZELAIC ACID CREAM BASED ETHOSOME - Apriani, Elsa Fitria; Nurleni, Novi; Nugrahani, Hervianti Nurfitria; Iskandarsyah, Iskandarsyah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Azelaic acid as an antibacterial to Propionibacterium acnes bacteria in recent years began to develop as an anti-acne using lipid bilayer vesicles to increase the penetration of azelaic acid to reach sebaceous tissue which is located in the dermis of skin where the growth of bacteria P. acnes. The development of azelaic acid in lipid bilayer vesicles is also due to the absorption of azelaic acid from cream preparations by only 4%. Azelaic acid gel based ethosomes also known give a larger zone of inhibition than azelaic acid creams and gels in the market. Methods: Preparation stability test of azelaic acid cream based ethosome was chemical and physical stability. The observed physics stability was organoleptic changes, homogeneity, pH, viscosity, cycling test, and mechanical test (centrifugal test). While chemical stability was performed to know the concentration of azelaic acid in cream to be periodically. Stability test was conducted for 12 weeks and observation every 2 weeks. Result: Physics stability test of that preparations was odorless, white, no change of phase, homogeneous, viscosity, and flow properties constant. While chemical stability test with the determination for 12 weeks to decreased content. However, these content is still included in the range of accuracy (90–110%). Conclusion: Azelaic acid of ethosome cream was physically and chemically stable.